Institutional Quality, Regulatory Environment and Microeconomic Performance: Evidence from Transition and Non-transition Developing Countries - Haggai Kennedy Ochieng; Bokyeong Park (East Asian Economic Review (EAER), 2021)
The development of regulatory systems varies between transition and non-transition economies. This suggests that they provide different incentives for entrepreneurial development and could have varied effects on the economy because they have different methods to deal with market failure. However, limited empirical evidence exists to prove the assumption of dichotomy. Using comprehensive data for institutional quality, labor market and financial market development, this research sought to analyze their effect on employment growth at micro level. The results show that the quality of institutions in transition economies are poorer relative to those in non-transition economies, but their financial and labor markets are more developed than the latter. Further analysis for the transition sample shows that the three variables are individually positively related with employment growth. For the non-transition sample, institutional quality and labor market flexibility bear a positive and significant effect on employment. Financial market development enters the model with a negative coefficient when regressed alone, but a joint test of significance finds that all the variables have a positive effect on employment growth. This result could imply that there is interdependence between institutional quality, labor flexibility and financial market development in firm-employment-growth relationship, or complementarity between regulations and the quality of institutions. Alternatively, this finding suggests that a stringently regulated credit market in non-transition economies have a selection effect-allocating credit only to entrepreneurs who already demonstrate strong growth potential. In sum, despite differences in the evolution of regulatory environment between the two samples, both of them complement employment growth at firm level. The overall implication of these findings is that less rigid regulations and coherent policies that are enforced with impartiality provide incentives for firms to expand.
Keywords: D02; D23; J08; 330; Institutional Quality; Labor Market Flexibility; Financial Market Development; Transition Economies; Non-transition Economies